KERJASAMA PENYULUH AGAMA ISLAM FUNGSIONAL DENGAN APARAT KELURAHAN DALAM MENGATASI PENYAKIT MASYAKARAKAT DI KELURAHAN PURUS KECAMATAN PADANG BARAT KOTA PADANG - Syafriwaldi Syafriwaldi (IAIN Batusangkar, 2018)
This paper raises the problem of how the cooperation of the Functional Islamic Counselor with Urban Officials in overcoming the disease of the community in Purus Village, Padang Barat Subdistrict, Padang City. Limitation of research is Cooperation extension of Islam functional with the village officials in overcoming drugs. Religious and village officials face many problems, such as multi talent community, stubborn, unruly and so on. Departing from the background above, it needs an in-depth study of the Cooperation of Functional Islamic Counselor with Urban Officials in Overcoming Community Disease. This research is a descriptive field research, aiming to describe reality in the field with qualitative and rationalistic approach. Data source 19 people Extension of Islamic Religion Functional PNS and Non PNS, Official apparatus, community leaders in Purus Village. Cooperation of extension of functional Islam with the urban village apparatus in overcoming drugs in Purus urban village only oriented to preventive measures. There is no action or curative cooperation.